Complementary therapies for older people in care - Tay, Sharon (Singing Dragon, 2014)
An invaluable companion for complementary and beauty therapists working with older people in care, this book offers helpful information and advice on practical issues that are often overlooked in training, including: ·Assessing older clients for appropriate treatments·Communicating effectively with older clients, relatives and care staff·Adapting treatments for older clients with particular health conditions, including dementia·Working around beds, wheelchairs, walking frames and medical equipment·Hygiene, safety and ethical considerations·Guidance on using specific complementary therapies and.